Photophysical and photochemical insights of the photodegradation of norfloxacin: The rate-limiting step and the influence of Ca2+ ion. (March 2019) - Zhang, Heming; Song, Xuedan; Liu, Jianhui; Hao, Ce
Abstract: Photodegradation is one of the major degradation paths for antibiotics as aquatic micropollutants in surface water. The photodegradation involves a number of complicated photophysical and photochemical processes. Exploration for the rate-limiting step among these processes can be essential for the elimination of antibiotics. In this work norfloxacin was selected as a target compound. The rate constants of photophysical transitions and their competitions were discussed under the framework of Fermi Golden rule and time-depended perturbation theory. Using density functional theory, the reaction paths in triplet state were searched. The competitions among the photophysical transitions and photochemical reaction paths indicate the intersystem crossing (ISC) from the S1 state to T1 state is the rate-limiting step in the aquatic photodegradation of norfloxacin. Ca 2+ ion significantly accelerates this bottleneck by coordinating with the carbonyl and carboxyl groups of norfloxacin. The coordination creates more ISC paths to triplet states and increases the spin-orbit coupling, Huang-Rhys factors, and the vibrational coupling of the ISCs. Graphical abstract: Image 1 Highlights: Comprehensively studied photophysical and photochemical processes of Norfloxacin. Identified intersystem crossing as the rate-limiting step of photodegradation. Enhanced photophysical characteristics by Ca 2+ ion. Theoretical exploration under the framework of Fermi Golden rule.